Relationship Between Neutrophil Gelatinase-Associated Lipocalin (NGAL) Levels and Inflammatory Bowel Disease Type and Activity - KOÇHAN, KORAY; Yesil, Atakan; GÖNEN, Can; Senates, Ebubekir; Paker, Nurcan; Gokden, Yasemin; Kochan, KORAY; Erdem, Emrullah Duzgun; Gunduz, Feyza (My University, 2013)
Background and Aim Neutrophil gelatinase associated lipocalin (NGAL) is a recently identified molecule, which is bacteriostatic, has tissue destructive effects and is proinflammatory with chemoattractant molecule binding properties. Our aim was to investigate the relationship between serum NGAL levels and the type and level of disease activity of IBD.